A volumetric and viscometric study of 4-aminobutyric acid in aqueous solutions of metformin hydrochloride at 308.15, 313.15 and 318.15 K - KRISHA RAJAGOPAL (Journal of the Serbian Chemical Society, 2011)
Density (r) and viscosity (h) measurements were performed for4-aminobutyric acid in 0.05, 0.10 and 0.15 M aqueous metformin hydrochloride at 308.15, 313.15 and 318.15 K. The measured values of density and viscosity were used to estimate some important parameters, such as the partial molal volume, Vf, the standard partial molal volume, Vf, the standard partial molal volume of transfer, DVf, the hydration number, nH, the second derivative of the infinite dilution of the standard partial molal volume with temperature ¶2Vf/¶T2, the viscosity B-coefficients, variation of B with temperature, dB/dT, the free energy of activation per mole of solvent Dm1* and solute Dm2* of the amino acid in a ternary system. These parameters were interpreted in terms of solute–solute and solute–solvent interactions and structure making/breaking ability of solutes in the given solution.